2016
DOI: 10.2522/ptj.20150166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pilates-Based Core Stability Training in Ambulant People With Multiple Sclerosis: Multicenter, Assessor-Blinded, Randomized Controlled Trial

Abstract: Participants did not improve significantly, either in the short term or at the 4-week follow-up, on the 10MTW after 12 weeks of Pilates exercises compared with 12 weeks of relaxation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 35 publications
1
60
0
5
Order By: Relevance
“…Other smaller studies have also shown that incorporating trunk exercises or Pilates exercises can be beneficial for PwMS [64, 65]. On the other hand a recent study showed that Pilates based core stability exercises had no effect on 10-meter walking, the MSWS-12, or the ABC scale compared to relaxation exercises [66]. In the beginning of the intervention period in the present study focus was on activating the deep abdominal muscles in neutral spinal alignment.…”
Section: Discussionmentioning
confidence: 72%
“…Other smaller studies have also shown that incorporating trunk exercises or Pilates exercises can be beneficial for PwMS [64, 65]. On the other hand a recent study showed that Pilates based core stability exercises had no effect on 10-meter walking, the MSWS-12, or the ABC scale compared to relaxation exercises [66]. In the beginning of the intervention period in the present study focus was on activating the deep abdominal muscles in neutral spinal alignment.…”
Section: Discussionmentioning
confidence: 72%
“…Individually tailored programmes supervised by a physiotherapist covering both motor and sensory strategies were found to improve balance performance and reduce the number of falls more e ciently than motor strategies alone [10,11]. Another therapeutic strategy is exercise focused on core stability exercise [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative information on pathology‐specific trunk instability during gait may help to develop the following: (1) interventions aimed at restoring physiologic trunk movements using traditional approaches and/or (2) instrumental systems able to measure trunk motion in real‐time and provide feedback information to the user during balance and gait rehabilitation …”
Section: Discussionmentioning
confidence: 99%